2012
DOI: 10.3233/jad-2011-102004
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal Inflammation in Relation to Cognitive Function in an Older Adult Danish Population

Abstract: Inflammation plays a significant role in Alzheimer's disease (AD) pathogenesis. Studies have shown that systemic, peripheral infections affect AD patients. Cognitive dysfunction is a consistent finding in AD and periodontal disease is a chronic, peripheral infection often resulting in tooth loss. We hypothesized that older adults with periodontal inflammation (PI) or many missing teeth would show impaired cognition compared to subjects without PI or with few missing teeth, and among subjects with PI, those wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
95
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(99 citation statements)
references
References 0 publications
4
95
0
Order By: Relevance
“…Epidemiological data indicate a slightly inverse relationship between TNF-α level and cognitive function in the 50 to 60-year old of healthy subjects [28]. Chronic inflammatory disease exerts detrimental effects on cognitive function for persons with chronic periodontal inflammation [29]. High IL-1 level in hippocampus impairs learning ability [30].…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological data indicate a slightly inverse relationship between TNF-α level and cognitive function in the 50 to 60-year old of healthy subjects [28]. Chronic inflammatory disease exerts detrimental effects on cognitive function for persons with chronic periodontal inflammation [29]. High IL-1 level in hippocampus impairs learning ability [30].…”
Section: Discussionmentioning
confidence: 99%
“…Since most studies have been cross-sectional and conducted primarily in older adults (4,8,9,1218), the possibility exists that poor nutritional status resulting from tooth loss may negatively affect cognitive ability (18,19). Cognitive dysfunction may lead to poorer self-care, thereby worsening oral health status (20).…”
Section: Introductionmentioning
confidence: 99%
“…Whereas many studies report associations of fewer teeth and complete tooth loss with poorer cognitive function (3,5,14,2224), evidence regarding the association between actual periodontal disease and cognitive ability is mixed (3,68,14,15). Furthermore, periodontal disease exposure in earlier studies has been assessed with measures, such as the community periodontal index (CPI), which are based on clinical signs that do not provide much information about the underlying biology of periodontal disease (7).…”
Section: Introductionmentioning
confidence: 99%
“…A further recent European study of 152 dentate 70-year-old subjects in Denmark found that those with periodontal inflammation had lower scores in tests of cognitive function (Kamer et al 2012). Periodontal inflammation was equated with pocketing 4 mm affecting 10% of the remaining teeth and so did not meet the threshold set in the current review for periodontitis.…”
Section: Commentmentioning
confidence: 99%